The golden compass - Pullman, Philip, 1946- (New York : Alfred A. Knopf, 1998)
Accompanied by her daemon, Lyra Belacqua sets out to prevent her best friend and other kidnapped children from becoming the subject of gruesome experiments in the Far North.
"A Knopf paperback"--T.p.
Originally published as: Northern lights.
Notable/Best Books (A.L.A.).
Wilson's Junior High School.
Wilson's Senior High School.
6.7.
Keywords: Fantasy; Kidnapping -- Fiction; Missing persons -- Experiments -- Fiction; Kidnapping -- Fiction; Missing persons -- Experiments -- Fiction; Arctic regions -- Fiction; Arctic regions -- Fiction; Fantastic fiction